Effect of Lignite Fly Ash on the Growth and Reproduction of Earthworm Eisenia fetida - S. Sarojini; S. Ananthakrishnasamy; G. Manimegala; M. Prakash; G. Gunasekaran (E-Journal of Chemistry)
Fly ash is an amorphous ferroalumino silicate, an important solid waste around thermal power plants. It creates problems leading to environmental degradation due to improper utilization or disposal. However, fly ash is a useful ameliorant that may improve the physical, chemical and biological properties of soils and is a source of readily available plant macro and micronutrients when it is used with biosolids. Supply of nutrients from fly ash with biosolids may enhance their agricultural use. The growth and reproduction of Eisenia fetida was studied during vermicomposting of fly ash with cowdung and pressmud in four different proportions (T1,T2,T3 & T4) and one control i.e., cow dung and pressmud alone. The growth, cocoon and hatchlings production were observed at the interval of 15 days over a period of 60 days. The maximum worm growth and reproduction was observed in bedding material alone. Next to that the T1 was observed as the best mixture for vermiculture.